Modeling and simulation of blood flow analysis on simplified aneurysm models - Lim, Sheh Hong; Mohd Azrul Hisham, Mohd Adib; Muhammad Uzair, Matalif; Mohd Shafie, Abdullah; Nur Hartini, Mohd Taib; Radhiana, Hassan (IOP Publishing, 2020)
Nowadays, the cerebral aneurysm is an abnormal focal dilation of a brain artery which is considered as a serious and potentially life-threatening condition. The rupture of an aneurysm causes subarachnoid hemorrhage (SAH) and is associated with high rates of morbidity and mortality. A better understanding of the mechanisms underlying aneurysm pathophysiology is crucial for the development of new preventive procedures and therapeutic strategies. This study focuses on the modeling and simulation of the blood flow analysis using simplified aneurysm models to perform early prediction on the geometrical effects of hemodynamics. The investigation involves three simplified models of aneurysms reconstructed using Solidworks 2019, in which the aneurysms are developed at the bifurcation. The qualitative comparison of the hemodynamics between three models was obtained and the geometrical effects were evaluated. The results show that the differences in shape and geometry on aneurysms affect the hemodynamics trend and are capable to apply for further understanding of problems regarding hemodynamics in the patient.